Adsorption of Cr(III) from Aqueous Solution using Borax Sludge - Senberber, Fatma Tugce; Yildirim, Meral; Mermer, Nevin Karamahmut; Derun, Emek Moroydor (SLOVENSKO KEMIJSKO DRUSTVO, 2017)
Borax sludge is the waste produced by a trommel sieve in the borax production process and is used as an adsorbent for Cr(III) removal. The effects of various parameters, including pH, initial Cr(III) concentration and contact time were investigated for batch adsorption of Cr(III). The experimental results obtained were applied to different adsorption isotherms and kinetic models. The results indicated that the Temkin isotherm (R-2 = 0.9749) was most suitable to explain the adsorption characteristics of borax sludge, and the removal of Cr(III) was achieved by a physisorption process. The overall kinetic data fitted the pseudo-second order rate model (R-2 = 0.9990). According to thermodynamic studies, which were carried out at different temperatures, changes in enthalpy (Delta H) and entropy (Delta S) values for Cr(III) adsorption by borax sludge were determined to be 69.395 kJ/mol and 0.276 kJ/mol K, respectively. The study implied that borax sludge could be used as an alternative adsorbent in the adsorption of Cr(III) from aqueous solutions.
Keywords: Adsorption kinetic; borax sludge; Cr (III); thermodynamic; WASTE-WATER; HEXAVALENT CHROMIUM; CR(VI); KINETICS; REMOVAL; THERMODYNAMICS; EQUILIBRIUM; ISOTHERMS; TRIVALENT; BEADS; Chemistry